The effect analysis of mediation variable of task productivity on the self-efficacy and employees’ performance - Annissa Chairum Soebandono; Levi Nilawati (Journal of Economics, Business, and Accountancy Ventura, 2016)
This research was conducted for analyzing the effect of mediating variable that is individual task proactivity as one of the proactivities of behavior towards the relationship between self-efficacy and the employees’ performance in the logistics companies of shipping the goods. It uses convenience sampling, which is a non-probability sampling method for getting the sample of 52 employees. They were divided into two divisions, namely infrastructure and quality assurance. The questionnaire consists of two parts, in which some were assessed by themselves and others that were assessed by the supervisor. They were analyzed using path analysis using analytical tools developed by Hayes, Preacher-Hayes with the simple mediation models. It was found that employees have self-efficacy, individual task proactivity, and relatively high performance, in which individual task proactivity can be a mediating variable on the effect self-efficacy on performance.